Impact of bosentan on health-related quality of life and dyspnoea in idiopathic pulmonary fibrosis: the BUILD-1 trial - Raghu, Ganesh (2009)
OBJECTIVE: No therapy is known to improve health-related quality of life (HRQL) or dyspnoea in patients with idiopathic pulmonary fibrosis (IPF). This study investigated longitudinal changes in HRQL and dyspnoea and explored the effects of bosentan on these endpoints during the BUILD-1 trial. METHODS: In total 154 subjects received oral bosentan (n=71) or placebo (n=83). Changes in HRQL and dyspnoea from baseline to month 6 (M6) and up to month 12 (M12) were measured using the St George's Respiratory Questionnaire (SGRQ), Short-Form 36-item instrument (SF-36), Transition Dyspnoea Index, and Borg Dyspnoea Index. RESULTS: Overall, minimal changes occurred in measures of HRQL and dyspnoea among placebo-treated subjects during the study. Effects of bosentan treatment on HRQL and dyspnoea in the all-treated population were minimal. However, in the subset of subjects who underwent surgical lung biopsy (SLB) for diagnosis of IPF, treatment effects were observed up to M12 in the Impacts domain of the SGRQ and the Physical functioning, General health and Role emotional domains of the SF-36. CONCLUSIONS: HRQL and dyspnoea changed minimally during the course of the study. Observations from exploratory analyses suggest benefits of bosentan on HRQL among patients who underwent SLB for diagnosis and merit further investigation.